The role of forensic economic expertise in the investigation of corruption crimes - Parfentii, L. A.; Парфентій, Л. А. (Socio-Economic Challenges: Proceedings of the International Scientific and Practical Conference ( Sumy, 14-15 November 2022). – Sumy : Sumy State University, 2022. – P. 74-76, 2022)
Розкрито роль судово-економічної експертизи в розслідуванні корупційних злочинів.

The role of forensic economic examination in the investigation of corruption crimes is revealed.

Раскрыта роль судебно-экономической экспертизы в расследовании коррупционных преступлений.
Keywords: Україна; forensic economic expertise; investigation of corruption crimes; corruption; Ukraine; судово-економічна експертиза; розслідування корупційних злочинів; корупційні злочини; корупція; Украина; судебно-экономическая экспертиза; расследование коррупционных преступлений; коррупция